2009
DOI: 10.5194/bgd-6-7627-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The interaction of ocean acidification and carbonate chemistry on coral reef calcification: evaluating the carbonate chemistry Coral Reef Ecosystem Feedback (CREF) hypothesis on the Bermuda coral reef

Abstract: Abstract. Despite the potential impact of ocean acidification on ecosystems such as coral reefs, surprisingly, there is very limited field data on the relationships between calcification and carbonate chemistry. In this study, contemporaneous in situ datasets of carbonate chemistry and calcification rates from the high-latitude coral reef of Bermuda over annual timescales provide a framework for investigating the present and future potential impact of rising pCO2 and ocean acidification on coral reef ecosystem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 113 publications
2
20
0
Order By: Relevance
“…Previous studies of Bermuda reef biogeochemistry have included observations of CO 2 -carbonate chemistry Bates, 2002), reef biogeochemical processes (Bates et al, 2010;Courtney et al, 2016) and longer-term proxy assessments of pH (Goodkin et al, 2015). For example, Bates et al (2010) reported a seasonal reduction in coral calcification (i.e., coral skeletal growth rates) with reduced carbonate ion [CO 2− 3 ] and aragonite , contributing further evidence to linkage of OA to declining coral calcification. They also highlighted the strong seasonal coupling and feedback between rates of coral calcification (i.e., coral skeletal growth and water assessment of net ecosystem calcification, NEC), other ecological components of the reef system (i.e., macroalgae) and reef chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies of Bermuda reef biogeochemistry have included observations of CO 2 -carbonate chemistry Bates, 2002), reef biogeochemical processes (Bates et al, 2010;Courtney et al, 2016) and longer-term proxy assessments of pH (Goodkin et al, 2015). For example, Bates et al (2010) reported a seasonal reduction in coral calcification (i.e., coral skeletal growth rates) with reduced carbonate ion [CO 2− 3 ] and aragonite , contributing further evidence to linkage of OA to declining coral calcification. They also highlighted the strong seasonal coupling and feedback between rates of coral calcification (i.e., coral skeletal growth and water assessment of net ecosystem calcification, NEC), other ecological components of the reef system (i.e., macroalgae) and reef chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In the milieu of environmental issues that beset coral reef health and future viability, ocean acidification comingles with variability of natural conditions to influence coral reef biogeochemical processes such as calcification, photosynthesis, respiration and CaCO 3 dissolution. A suite of in situ, in vitro, experimental and model studies have shown decreases in both mature colony and juvenile coral calcification with reduced carbonate ion concentration [CO 2− 3 ] or aragonite saturation state (i.e., aragonite ) under natural and/or perturbed conditions (e.g., Gattuso et al, 1996Gattuso et al, , 1998Langdon et al, 2000;Langdon and Atkinson, 2005;Schneider and Erez, 2006;Anthony et al, 2008;Bates et al, 2010;Kroeker et al, 2010;Erez et al, 2011;Pandolfi et al, 2011;de Putron et al, 2011;Chan and Connolly, 2013;Kroeker et al, 2013a;Venn et al, 2013;Evenhuis et al, 2015). In other studies, bicarbonate ion concentration has been shown to be the primary modifier of coral calcification (e.g., Jury et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations